Conceptual history of the Near East: the Sattelzeit as a heuristic tool for interrogating the formation of a multilayered modernity - Zemmin, Florian; Sievert, Henning (Contributions to the history of concepts, 2021)
Conceptual history holds tremendous potential to address a central issue in Near Eastern Studies, namely the formation of modernity in the Near East, provisionally located between the mid-nineteenth and mid-twentieth centuries. The encounter with European powers, primarily Britain and France, was a decisive historical factor in this formation; and European hegemony is, in fact, inscribed into the very concept of “modernity,” which we take as an historical, rather than analytical, concept. The conceptual formation of modernity in Arabic and Turkish was, however, a multilayered process; involving both ruptures and continuities, intersecting various temporalities, and incorporating concepts from several languages. To interrogate this multilayered process, we suggest the metaphor of the Sattelzeit (Saddle Period) as a heuristic tool, precisely because of its being tied to modernity. Finally, the article will show what conceptual history of the Near East has to offer to conceptual history more broadly.